2022
DOI: 10.3390/app12042167
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Blocks Reinforced with Arundo donax Natural Fibers with Different Aspect Ratios for Application in Bioarchitecture

Abstract: In recent decades, the construction industry has advanced in its use of natural green resources, such as vegetable fibers (e.g., flax, hemp, jute, etc.) added in concrete mixtures, to create building materials that are both economically and environmentally sustainable. The pricing, low energy cost, and environmental sustainability of these natural fibers are driving this interest. The quantity of fibers and the ratio of fiber length to its transverse diameter (aspect ratio) are critical characteristics that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Farm buildings, have been investigated by scientific researches related to the valorisation of traditional material for architectural solutions (Picuno P., 2016), the development of new bio-materials (Castronuovo et al, 2015), etc. Several studies have discussed the materials and architectural solutions to use in green building, such as the research conducted by Manniello et al (2022), that analyzed the structural performance of a plant -considered as a weed, for urban and rural areas, such as Arundo donax L. -when used to lighten concrete bricks, showing positive results in mechanical tests (Fig. 2).…”
Section: Biosystems Engineering Techniques For Implementing Agroecologymentioning
confidence: 99%
“…Farm buildings, have been investigated by scientific researches related to the valorisation of traditional material for architectural solutions (Picuno P., 2016), the development of new bio-materials (Castronuovo et al, 2015), etc. Several studies have discussed the materials and architectural solutions to use in green building, such as the research conducted by Manniello et al (2022), that analyzed the structural performance of a plant -considered as a weed, for urban and rural areas, such as Arundo donax L. -when used to lighten concrete bricks, showing positive results in mechanical tests (Fig. 2).…”
Section: Biosystems Engineering Techniques For Implementing Agroecologymentioning
confidence: 99%
“…Consequently, it shows good mechanical properties (elastic modulus of about 40 GPa [35]) provided by the cellulose fraction, even if lower than those of some species of bamboo, and a reduced hydrophilicity on account of the reduced hemicellulose content. So far, Arundo has been employed in the formulation of polymer matrix composites (both thermosetting, i.e., epoxy, polyester and thermoplastics such as PE, PP and polylactic acid (PLA)) [34,[36][37][38][39] but its use in inorganic matrix has still to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Arundo donax is a common plant with a strong potential as a long-term structural plant. Many authors focus on using Arundo donax leaves in the building sector , mainly to obtain particleboards and concrete block , or epoxy resin reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Shon et al 23 found that when ADL fibers were mixed with cement mortars, the thermal conductivity and density of the concrete diminished. Manniello et al 24 tested the tensile strength of cylindrical concrete blocks at a constant amount of ADL fibers (1 wt %) and different aspect ratios of 30, 50, and 70 (mm/mm). They found that larger aspect ratios generate better tensile qualities of concrete composites.…”
Section: Introductionmentioning
confidence: 99%